HUBUNGAN TINGKAT PENGETAHUAN DENGAN TINGKAT KECEMASAN REMAJA PUTRI YANG PERNAH MENGALAMI DISMINORE (NYERI HAID) - Ridwan, Ahmad; Nur, Vivin (Jurnal AKP, 2011)
Disminorrhea are unpleasant experience by presence of pain in lower part of abdomen which may affect the daily activities. Menstrual pain is a symptom and it is not a disease itself. Almost all adolescent have experienced of it and may generate an anxiety particularly for the affected women, especially if their knowledge is insufficient. The lack of knowledge may trigger an anxiety and hence the higher the knowledge, the anxiety will decrease.This objective of this research was to know the influence of knowledge Â to level of Â anxiety of students of Senior High School of (SMA) Muhammadiyah I Pare which had had experienced of menstrual pain. This research used Cross Sectional technique and the populations of the research was student in SMA Muhammadiyah I Pare by sample were 30 respondents. Sampling technique was total sampling. Data was analyzed by Spearman correlationTheÂ  analyzedÂ  correlationÂ  ofÂ  spearmanÂ  rho got Ï (0,561)Â  above ( 0,05)Â  or Ï (0,561) ( 0,05). Its means H0 was accepted, H1 was rejected, meant there was no influence between level of knowledge to the level of anxiety of adolescence who had experienced of menstrual pain in SMA Muhammadiyah I Pare.The sufficient knowledge on dismenorrhea can degrade anxiety, knowledge can be obtained by read articles of about menstrual pain and the school should give the lesson of about system Â Â reproduction and can perform program of consultancy about their problem about reproductive system with health care institution or health care personals.Â